A Literature Survey on Big Data Deduplication: Integrating Access Management and Proxy Re-encryption for Deduplicating Encrypted Data in Cloud (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Big data primarily based Cloud computing offers a replacement method of service provision by re-arranging varied resources over the web. The foremost necessary and standard cloud service is information storage. So as to preserve the privacy of information holders, information are typically hold on in cloud in an encrypted kind. However, encrypted information introduce new challenges for cloud information de-duplication that becomes crucial for giant information storage and process in cloud. Ancient de-duplication schemes cannot work on encrypted information. Existing solutions of encrypted information de-duplication suffer from security weakness. They cannot flexibly support information access management [13] and revocation. Therefore, few of them is pronto deployed in observe. During this paper, we propose a theme to de-duplicate encrypted information hold on in cloud supported possession challenge and proxy re-encryption. It integrates cloud information de-duplication with access management.